Analisis Isi Pesan Dakwah Da’i Muda Husain Basyaiban di Kalangan Remaja Pengguna TikTok - Sintia Putri Andani; Parihat Kamil (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. This research explores the use of the TikTok social media platform as a method of Islamic preaching (dakwah), replacing traditional mosque-based learning. The TikTok account @Kadamsidik, with a large audience, serves as an effective platform for delivering dakwah messages to teenagers who are more inclined towards gadget-based activities. The study employs a qualitative descriptive method with data collection techniques such as documentation and observation. The findings, analyzed using Roland Barthes' Semiotic Analysis, reveal that Husain Basyaiban employs three dakwah methods: Al-Hikmah, Al-Mauidzah Al-Hasanah, and Al-Mujadalah bilati hiya al-ahsan. The dakwah messages in the TikTok content @Kadamsidik focus on the Islamic teachings trilogy: Aqidah, Syaria’h, and Akhlaq. The Syaria’h category stands out as the most dominant in the TikTok content. The implications of this research include the hope that students from the Faculty of Dakwah can conduct further analytical research across various media platforms such as videos, films, and books to enrich their knowledge. Additionally, it is encouraged for preachers (da'i) and the audience (mad'u) to utilize various social media networks, particularly TikTok, as a means to disseminate Islamic dakwah. Abstrak. Penelitian ini membahas penggunaan media sosial TikTok sebagai metode dakwah Islam, menggantikan pembelajaran di masjid. Akun TikTok @Kadamsidik, dengan audience yang besar, menjadi platform efektif untuk menyampaikan pesan dakwah kepada remaja yang cenderung lebih suka bermain gadget. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data dokumentasi dan observasi. Hasil penelitian menggunakan Analisis Semiotika Roland Barthes menunjukkan bahwa Husain Basyaiban menggunakan tiga metode dakwah: Al-Hikmah, Al-Mauidzah Al-Hasanah, dan Metode Al-Mujadalah bilati hiya al-ahsan. Pesan dakwah dalam konten TikTok @Kadamsidik terfokus pada trilogi ajaran Islam: Aqidah, Syaria’h, dan Akhlaq. Kategori video Syaria’h menjadi yang paling dominan. Implikasi penelitian ini mencakup harapan agar mahasiswa Fakultas Dakwah dapat melakukan penelitian analitis lebih lanjut dalam berbagai media, seperti video, film, dan buku, untuk memperkaya pengetahuan. Selain itu, para da'i dan mad'u diharapkan dapat memanfaatkan berbagai jejaring sosial, terutama TikTok, sebagai sarana untuk menyebarkan dakwah Islam.